According to the normal weight, overweight and obese comparison of bioelectric impedance analysis method with the other methods - Evrim Cakmakcı; Fatma Arslan; Hüsamettin Vatansev; Meryem Ayrancı (Türk Spor ve Egzersiz Dergisi)
Women are faced with the problem of obesity because of over-nutrition, still life and birth weight. To Assess overweight and obesity are used with Body mass index (BMI), waist circumference, waist/hip ratio and skinfold thickness measurement method and Bioelectrical impedance analysis method. The purpose of this study was to compare of the methods used to assess body composition in normal weight, overweight and obese in adults women. In this study participated adult women that the mean age of normal weight 25.70 ± 7.85 (N = 17), overweight 32.47 ± 8.22 (N = 36), obese 38.12 ± 8.95 (N = 40) and total N = 93. Subjects’ body composition were evaluated  with Body mass index, waist circumference, waist/hip ratio and skinfold thickness measurements and measured using bioelectric impedance analysis. For statically analysis, One Way Anova and Tukey tests were performed. Significance level was accepted as 0.05 for all tests. According to the results of anthropometric measurements was found BMI, waist circumference, and bioelectrical impedance analysis method for all the groups differ (p lt;0.05), waist / hip ratio values were found to be different between normal weight and obese groups (p lt;0.05) that participated in the research. Body mass index and bioelectric impedance are important methods to detect of obesity, and the waist circumference be used together these methods to determine the abdominal obesity may be more useful.